How fast hake grows? A study on the Mediterranean hake (Merluccius merluccius, L.) comparing whole otoliths readings and length frequency distributions data - García Rodríguez, Mariano; Esteban, Antonio (Scientia Marina, 2002)
The hake (M. merluccius) is a target species of the Mediterranean trawl fleets. In this study, its growth was compared by two means: whole otolith readings and length frequency distribution analysis. Two growth hypotheses, fast and slow, were assumed using the results of otolith readings: (1) two rings were formed every year and (2) a single ring was formed every year. The monthly length distributions covered the period from 1992 to 1998, and the otoliths were obtained from monthly samplings between 1992 and 1995. The variability observed in the results for the number of rings counted was shown especially in the range of lengths for each group of individuals that had the same number of rings. A high correlation was found between the rings counted in the otoliths and the length of the individual in cm. The sex factor did not influence the relationship, unless the sexually undifferentiated individuals were included. The best fit with the growth data according to the length frequencies occurred in the two-ring hypothesis (Hypothesis 1), meaning faster growth rates than had been accepted till now, especially in females. We suggest the consideration of the hypothesis of faster growth in future studies.